Information Literacy Of Lembak Traditional Chiefs To Young Generation In Panorama Village - Putra, Meriansyah Dwi; Yanto, Yanto; Octaviani, Vethy (Utami Publisher, 2025)
This research aims to describe information literacy in the customs of the Lembak community. This research is a qualitative study with data described descriptively. Various events on the subject under study are described in a series of words or sentences in an in-depth, structured and logical manner based on the research topic. Researchers must be able to describe the data obtained from research subjects thoroughly so as to form an in-depth understanding of a study. This research uses the Big Six theory. The research results show that the main obstacles in literacy of Lembak traditional information among the younger generation are infrastructure, finances, the response of the government itself, community figures, and also the younger generation who are less interested in knowing about Lembak culture. Moreover, there are electronic influences such as cell phones, television and then foreign cultural influences that are not in accordance with the norm. Based on the results of in-depth interviews with researchers, the younger generation prefers to seek cultural information through social media rather than attending traditional meetings or socialization.